THE INFLUENCE OF THE CULTURE OF LAW IN LAW ENFORCEMENT CRIMINAL ACTS IN THE FIELD OF FISHERIES - Asis, Abd; Sofyan, Andi; -, Aswanto; Sampurno, Slamet (Journal of Humanity, 2015)
Indonesia has the potential of marine and fisheries and a good variety of renewable or not renewable, but in the field fishery optimally still hampered with the rampant practice of catching fish illegally or criminal acts in the field of fisheries. The purpose of this writing is to know the influence of the culture of law in law enforcement criminal acts in the field of fisheries. Writing this type of normative research using secondary data, then the data were analyzed qualitatively-normative, examine the way interpret and construct the statement contained in document per-Act. The results showed that the law is strongly influenced by factors such as, among others: values, attitudes, and the communitys view of called with cultures of law. Based on legal cultures which may give rise to differences in law enforcement between the communities that one with other communities. The legal culture is linked to the professionalism of law enforcers in the exercise of his duties, and public awareness in adhering to the law itself. Overall attitudes and values and behavior that determine the applicable law on society. Thus, the construction of the legal awareness should be oriented in an effort to promote the values underlying the legislation in question as well as paying attention to the communication of the ruling factor in order for the contents of such laws can be known by the public at large as the target of the rule of law itself. So the culture of the law contains the meaning of the process of internalization of values that are alive and thriving in the community who can serve as a cornerstone in understanding and law enforcement especially in the field of fisheries. Therefore, the fundamental issues should be against the law as already described above should be addressed properly